2017
DOI: 10.1164/rccm.201603-0518oc
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study to Identify Single-Nucleotide Polymorphisms for Acute Kidney Injury

Abstract: Our findings reveal two genetic loci that are associated with acute kidney injury. Additional studies should be conducted to functionally evaluate these loci and to identify other common genetic variants contributing to acute kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…We used the genotyping v1.9.4 module clustering algorithm from Illumina GenomeStudio software for SNP calling (San Diego, California, USA). Patients with sample genotype call rate under 97% and patients with a discrepancy between X chromosome zygosity and reported sex were excluded (86). We extracted SNPs within a 2-Mb region surrounding the HP gene (Hg19 chr16:71,036,975-73,063,764), then phased the target region and imputed HP genotype using the Beagle version 3.3.2 algorithm (87) with a phased reference panel provided by Boettger et al (36).…”
Section: Methodsmentioning
confidence: 99%
“…We used the genotyping v1.9.4 module clustering algorithm from Illumina GenomeStudio software for SNP calling (San Diego, California, USA). Patients with sample genotype call rate under 97% and patients with a discrepancy between X chromosome zygosity and reported sex were excluded (86). We extracted SNPs within a 2-Mb region surrounding the HP gene (Hg19 chr16:71,036,975-73,063,764), then phased the target region and imputed HP genotype using the Beagle version 3.3.2 algorithm (87) with a phased reference panel provided by Boettger et al (36).…”
Section: Methodsmentioning
confidence: 99%
“…No consensus method exists to establish pre-AKI baseline serum creatinine in the absence of previous values (recent or distant) 4647. Furthermore, changes in serum creatinine are often delayed owing to renal reserve and the kinetics of AKI.…”
Section: Early Detection Of Sa-akimentioning
confidence: 99%
“…More recently a genome-wide association study of patients with AKI (including septic AKI) found that polymorphism of the likely controller of a transcription factor (on chromosome 4) involved in innate immunity pathways was associated with greater risk of AKI. Similarly, another gene involved in the likely control of transforming growth factor beta (on chromosome 22) was also associated with greater risk [23]. The outcomes of critically ill patients with sepsis [24] and AKI requiring RRT [25], however, have improved in recent years.…”
Section: Table 1 Criteria and Staging For Acute Kidney Injurymentioning
confidence: 99%